Antologi Puisi Membaca Lambang Analisis Citra Wilayah Pesisir - Andhika Martianto, Ridwan (Humanis; Vol 25 No 4 (2021), 2021)
This article discusses images of coastal areas from the poetry anthology Membaca Lambang by Acep Zamzam Noor. The focus of this research is two things, namely to reveal the structure and to reveal the image of the coastal area in the poetry anthology Membaca Lambang . The analysis technique used in this research is purposive sampling technique. The method used to collect data is the literature study method. Description method is used to analyze data. The analysis of the twelve poems which cover the use of structural theory (five strata of norms) from Roman Ingarden and literary ecology by Suwardi Endraswara. Based on the analysis, it was found that the anthology structure of Membaca Lambang poetry was formed into five norms, namely the first layer (sound), the second layer (meaning), the third layer (background, actors, and the world of the author), the fourth layer (world), and the fifth layer metaphysical. Furthermore, the image of the coastal area is clearly depicted in each poem. One of the reasons for this is through the use of diction such as bays, docks, ports, and beaches. The coastal areas that appear include, ecological images, elegance-humanity, and religiosity.